2006
DOI: 10.1017/s0265021506000330
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epidural bupivacaine on maintenance requirements of sevoflurane evaluated by bispectral index in children

Abstract: Combined anaesthesia with epidural bupivacaine maintains the same Bispectral index values as Balanced anaesthesia during orthopaedic surgery in children without fentanyl and with a lower sevoflurane requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
(27 reference statements)
2
21
1
Order By: Relevance
“…The BIS falls with caudal block during general anaesthesia (in older children, but not in infants) [24,25] and falls during spinal anaesthesia in infants [26].…”
Section: Bispectral Indexmentioning
confidence: 99%
“…The BIS falls with caudal block during general anaesthesia (in older children, but not in infants) [24,25] and falls during spinal anaesthesia in infants [26].…”
Section: Bispectral Indexmentioning
confidence: 99%
“…Lower end-tidal concentrations of sevoflurane were required when general anaesthesia was supplemented with caudal bupivacaine in paediatric patients. [9] Lidocaineadministered for epidural anesthesia has been reported to reduce the MAC of sevoflurane by approximately 50%. [5] Epidural morphine reduces the MAC of halothane by 28% and isoflurane by 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Regional anesthetic blocks are often used in combination with general anesthesia for pediatric surgery and have been shown to reduce general anesthetic requirements, pain, opioid use, and postoperative nausea and vomiting across a wide range of open surgical procedures [1][2][3][4]. It remains uncertain, however, if adjunctive regional anesthesia provides benefits to children undergoing laparoscopic or robot-assisted laparoscopic (RAL) surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It may also be secondary to less need for general anesthetic agents. Standardized measurement of inhalational anesthetic requirements is not feasible in a retrospective study such as this, but two prospective trials of children undergoing lower extremity procedures demonstrated that caudal blocks decrease sevoflurane consumption[1,2].…”
mentioning
confidence: 99%